Early Age Hydration Characteristics of Calcium Sulphoaluminate Cement Mortar Cured at a Temperature Range from −10 to 20°C - Zhongyu Chen; Jianhong Fang; Feng Ming; Yuhang Liu (Advances in Materials Science and Engineering)
With the increasing number of infrastructures constructed in marine and cold regions, research on and applications of calcium sulphoaluminate (CSA) cement have been flourished, but the hydration process of CSA at low temperature has not been systematically investigated. To characterize the influence of low temperature on the hydration characteristics, freshly mixed CSA mortars were cured at −10, −5, 0, 5, and 20°C, respectively. The hydration process was investigated by electrical resistivity, compressive strength, and microstructure analyses. Results show that the hydration process (especially the induction period) is lengthened by low curing temperature. Both the electrical resistivity and compressive strength increase with an increase in the curing temperature. The compressive strength was reduced at a low curing temperature. Among these five curing temperatures, 5°C is the optimal curing temperature. Low temperatures do not change the kinds of hydrates, but reduce their amount. The scanning electron microscopy results illustrate that fewer hydrates fill the pores in specimens cured at low temperatures, while more hydrates form at higher temperatures. Moreover, low curing temperature contributes to the formation of coarse ettringite crystals. For the cement used at low temperature, the induction period should be reduced by adjusting the calcining process and composition proportion.